Goodrich Castle
Goodrich castle on the borders of South Wales was extended during this period. Already fortified by a square Norman keep, it was surrounded by a massive curtain wall protected by corner towers wall, arranged to pick up the warmth of the sun from windows facing the inner courtyard, was this large room, hopefully looking forward to days of ease. Such spaces were called solars.